English teacher’s difficulties in designing lesson plan based on Indonesian 2013 curriculum - Nurfitri Nurfitri; Regina Regina; Ryani Yulian (Journal of English Language Teaching Innovations and Materials (Jeltim), 2020)
The aim of this research was to gain deeper understanding concerning English teacher's difficulties in designing lesson plan based on the 2013 Curriculum. This qualitative case study employed observation, interview and document analysis. The instruments of collecting data consisted of observation checklists, an interview guide and field notes. The subject was one English teacher at SMP Negeri X Singkawang who has implemented the 2013 Curriculum. This research revealed that English teacher encountered difficulties in designing lesson plan based on  2013 curriculum on three stages. In pre design stage, the teacher found the difficulties in term of inability to formulate and design lesson plan due to limited time constraints. In whilst design stage, the English teacher experienced difficulties in assessment with many variables. In post-design stage, the English teacher coped with students’ reluctance in the teaching learning proces since the learning process was not appropriate with the lesson plan and lacked of facilities at school. It is recommended that the teacher should put more efforts to improve professional competencies by participating in activities such as training and workshop and accelerate knowledge improvement, creativity and technology to be able to apply the 2013 curriculum effectively.